Antibody response durability following three-dose coronavirus disease 2019 vaccination in people with HIV receiving suppressive antiretroviral therapy. (1st April 2023) - Lapointe, Hope R.; Mwimanzi, Francis; Cheung, Peter K.; Sang, Yurou; Yaseen, Fatima; Speckmaier, Sarah; Barad, Evan; Moran-Garcia, Nadia; Datwani, Sneha; Duncan, Maggie C.; Kalikawe, Rebecca; Ennis, Siobhan; et al.
Abstract : Background: Limited data exist regarding longer term antibody responses following three-dose coronavirus disease 2019 (COVID-19) vaccination, and the impact of a first SARS-CoV-2 infection during this time, in people with HIV (PWH) receiving suppressive antiretroviral therapy (ART). We quantified wild-type-specific, Omicron BA.1-specific and Omicron BA.5-specific responses up to 6 months post-third dose in 64 PWH and 117 controls who remained COVID-19-naive or experienced their first SARS-CoV-2 infection during this time. Design: Longitudinal observational cohort. Methods: We quantified wild-type-specific and Omicron-specific anti-Spike receptor-binding domain IgG concentrations, ACE2 displacement activities and live virus neutralization at 1, 3 and 6 months post-third vaccine dose. Results: Third doses boosted all antibody measures above two-dose levels, but BA.1-specific responses remained significantly lower than wild-type-specific ones, with BA.5-specific responses lower still. Serum IgG concentrations declined at similar rates in COVID-19-naive PWH and controls post-third dose (median wild-type-specific and BA.1-specific half-lives were between 66 and 74 days for both groups). Antibody function also declined significantly yet comparably between groups: 6 months post-third dose, BA.1-specific neutralization was undetectable in more than 80% of COVID-19 naive PWH and more than 90% of controls. Breakthrough SARS-CoV-2 infection boosted antibody concentrations and function significantly above vaccine-induced levels in both PWH and controls, though BA.5-specific neutralization remained significantly poorer than BA.1 even post-breakthrough. Conclusion: Following three-dose COVID-19 vaccination, antibody response durability in PWH receiving ART is comparable with controls. PWH also mounted strong responses to breakthrough infection. Due to temporal response declines, however, COVID-19-naive individuals, regardless of HIV status, would benefit from a fourth dose within 6 months of their third.